2021
DOI: 10.3389/fphar.2021.773834
|View full text |Cite
|
Sign up to set email alerts
|

Ferruginol Restores SIRT1-PGC-1α-Mediated Mitochondrial Biogenesis and Fatty Acid Oxidation for the Treatment of DOX-Induced Cardiotoxicity

Abstract: Background: Doxorubicin (DOX), a broad-spectrum chemotherapy drug, has life-threatening cardiotoxicity. Therefore, searching cardioprotective drugs for DOX-induced cardiotoxicity (DIC) is urgently needed.Objectives: This study aimed to explore cardioprotective effect and specific mechanism by which Ferruginol (FGL) attenuated DIC in vivo and in vitro.Methods: We evaluated the cardioprotection of FGL and performed high-throughput RNA-Seq on a DIC mouse. Whereafter, multiple methods, including western blot, RT-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Ferruginol effectively attenuated myocardial injury caused by overdosed isoprenaline hydrochloride by reducing cardiac injury markers: cardiac troponin-T (cTnT), cardiac troponin-I (cTnI), creatine kinase (CK), and creatine kinase-MB (CKMB) in myocardial infarction model [ 44 ]. This finding supports the latest study by Li et al [ 45 ] that demonstrated that ferruginol reduced cardiac injury markers in the doxorubicin (DOX)-induced cardiotoxicity model. Furthermore, ferruginol exerted its antioxidant properties in the reduction of lipid peroxidation markers and malondialdehyde (MDA) and upregulated the antioxidant enzymes SOD, GPx, catalase (CAT), and glutathione (GSH).…”
Section: Role Of Terpenophenolic Compounds On Inflammation and Apopto...supporting
confidence: 91%
“…Ferruginol effectively attenuated myocardial injury caused by overdosed isoprenaline hydrochloride by reducing cardiac injury markers: cardiac troponin-T (cTnT), cardiac troponin-I (cTnI), creatine kinase (CK), and creatine kinase-MB (CKMB) in myocardial infarction model [ 44 ]. This finding supports the latest study by Li et al [ 45 ] that demonstrated that ferruginol reduced cardiac injury markers in the doxorubicin (DOX)-induced cardiotoxicity model. Furthermore, ferruginol exerted its antioxidant properties in the reduction of lipid peroxidation markers and malondialdehyde (MDA) and upregulated the antioxidant enzymes SOD, GPx, catalase (CAT), and glutathione (GSH).…”
Section: Role Of Terpenophenolic Compounds On Inflammation and Apopto...supporting
confidence: 91%
“…G-Rb3, the main component of Sanqi, was shown to e a protective effect on the myocardium by improving energy metabolism, suppressing idative stress and improving microcirculation disorders [18,20,37]. FGL is a natural p phenol and terpenoid compound that was shown to play a cardioprotective role in mod of doxorubicin-induced myocardial injury [31]. Owing to the complexity of serious eases, such as myocardial infarction, recent developments have gradually shifted fro focus on monotherapy to combined or multiple therapies because the synergy of th peutic agents or techniques results in ostentatious super additive (namely "1 + 1 > MI results from the irreversible death of cardiomyocytes which caused by prolonged hypoxia or inadequate blood supply [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, our research found that G-Rb3 exerts a cardio-protective effect by inhibiting apoptosis and up-regulating energy metabolism [18]. FGL restores mitochondrial biogenesis and FAO for the treatment of doxorubicin-induced cardiotoxicity [31]. However, whether FGL can improve the effectiveness of G-Rb3 in the treatment of myocardial infarction remains unclear.…”
Section: Introductionmentioning
confidence: 87%
“…Increased mitochondrial biogenesis was observed in DOX-treated mice that received ferruginol, a pharmacological activator of PPARγ coactivator 1 alpha (PGC-1α), the master regulator of mitochondrial biogenesis. This was associated with increased fatty acid oxidation, mitochondrial function, and myocardial integrity [65].…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%